Calibration of the Logarithmic-Periodic Dipole Antenna (LPDA) Radio Stations at the Pierre Auger Observatory using an Octocopter - The Pierre Auger Collaboration; Allekotte, Ingomar; Andrada, B.; Asorey, Hernán Gonzalo; Avila, G.; Bertou, Xavier Pierre Louis; Botti, Ana Martina; Cancio, A.; Cobos, A.; Contreras, F.; Dasso, Sergio Ricardo; Dova, Maria Teresa; et al. (IOP Publishing, 2017)
Fil: The Pierre Auger Collaboration. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Oficina de Coordinacion Administrativa Pque. Centenario. Instituto de Tecnologia En Deteccion y Astroparticulas. Itedam - Subsede del Instituto de Tec. En Deteccion y Astroparticulas Mendoza | Comision Nacional de Energia Atomica. Instituto de Tecnologia En Deteccion y Astroparticulas. Itedam - Subsede del Instituto de Tec. En Deteccion y Astroparticulas Mendoza | Universidad Nacional de San Martin. Instituto de Tecnologia En Deteccion y Astroparticulas. Itedam - Subsede del Instituto de Tec. En Deteccion y Astroparticulas Mendoza. ; Argentina; Argentina. Observatorio Pierre Auger; Argentina